Consolidation Effect of Prefabricated Vertical Drains with Different Lengths for Soft Subsoil under Vacuum Preloading. (19th August 2019) - Lou, Chenhui; Ni, Junfeng; Chai, Jingchun; Fu, Hongtao; Hu, Xiuqing; Xu, Donghai; Lyu, Youchang; Guan, Zhi; Xia, Zhengde; Ye, Qiang
Abstract : The application of vacuum preloading to prefabricated vertical drains (PVDs) with different lengths is widely used in practical engineering to investigate their consolidation at the same depths of even and multilayer subsoils from the seabed. In a laboratory, model experiment was conducted using even subsoil and embedded PVDs with lengths of 0.6 and 1.2 m. The obtained results showed that in the even subsoil, the 1.2 m PVDs maintained a higher vacuum pressure in the shallow layer and demonstrated better consolidation behavior as compared to those of the 0.6 m PVDs. In the upper subsoil layer, the average vane shear strengths of these two systems increased to 18.2 and 22.6 kPa, respectively. The degree of consolidation of the upper subsoil layers in the two model experiments calculated from the pore water pressures under boundary drainage conditions were 51% and 68%, respectively. For practical verification purposes, similar experiments were conducted for multilayer subsoil by inserting PVDs with lengths of 6 and 15 m into different test sites. As a result, the vane shear strengths of the upper 6 m subsoil layers increased to 26.3 and 33 kPa, while the degree of consolidation were 72.1% and 80.9%, respectively, although some irregularities were observed at different depths.